Characterization of soils cultivated with cassava under different managements - Andrezza G. Costa; Luciano da S. Souza; Francisco A. da S. Xavier; Alide M. W. Cova; Evellyn F. da Silva; Marcela R. Bonfim (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Although cassava is an undemanding crop in terms of soil chemical fertility, the scarcity of nutrients affects crop productivity, and it is common to cultivate it in soils with low natural fertility, as occurs in Coastal Tablelands. In this context, the present study aimed to evaluate the physical and chemical attributes of soils cultivated with cassava under different managements. The study was carried out in the municipality of São Felipe, located in the landscape unit of Coastal Tablelands, Bahia state, Brazil. Fifteen properties were selected to evaluate the characteristics of soils cultivated with cassava under different types of management. Soil sampling was carried out during the months of October and November 2018, a dry period in the region. The medium-textured soil was predominant in the different areas of management of cassava cultivation. Most areas showed pH below the recommended range for cassava (5.5 to 6.5), base saturation below 50% and low phosphorus, potassium, calcium, and magnesium contents, according to the crop’s nutritional needs. The first two principal components explained 84.65% of the total variance. Thus, it was possible to verify that the diversity of management of cassava production areas results in high or very high variability of soil chemical attributes. The attributes pH, P, Al, H + Al, V, CEC and OM are the most representative in the distinction of soils of the cassava cultivation areas evaluated.